Association of PC and AT levels in the early phase of STEMI treated with pPCI with LV systolic function and 6-month MACE. Issue 6 (2nd November 2021) - Obradovic, Slobodan; Begic, Edin; Jankovic, Slobodan; Romanovic, Radoslav; Djenic, Nemanja; Dzudovic, Boris; Jovic, Zoran; Malovic, Dragana; Subota, Vesna; Stavric, Milena; Ljuca, Farid; Kusljugic, Zumreta
ABSTRACT: Objectives : To examine a relationship between protein C (PC) and antithrombin III (AT III) activities with ejection fraction of left ventricle (EFLV), in the early phase of acute ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI), and to investigate whether PC and AT III are associated with major adverse cardiovascular events (MACE) within 6 months following from pPCI. Patients and methods : The research had a prospective character and included 357 patients who had, following the diagnosis of the STEMI, undergone pPCI at the Clinic of Cardiology and Emergency Internal Medicine, Military Medical Academy, Belgrade, Serbia, from January 2010 until April 2019. Results : The EFLV positively correlated with PC values (rho = 0.229). There was a statistically significant increase in the PC values between patients with MACE compared with those without MACE at 6 months' follow-up evaluation (p < 0.0001). Also, significant difference in PC values between patients who died in hospital and those who were alive at 6 months' follow-up (p < 0.01) was observed. PC values were different across different EFLV groups (p < 0.001), increasing from the 1 st to the 4 th EFLV quartiles: the median and the interquartile values for the 1 st, 2 nd, 3 rd and 4 th quartiles were 1.0400IU/l ± 0.15, 1.1400IU/l ± 0.15, 1.1350IU/l ± 0.16 and 1.2200IU/l ± 0.14, respectively. Conclusion : Increased PC activity in the early phase of STEMI is associated with higher EFLV 5 days after the pPCI as well as with MACE at 6 months after the pPCI.